Persuasive Communication by the Prio Utomo Association in Motivating Men to Undergo Vasectomy - Dwinda Sekar Andrea; Hapsari Dwiningtyas (Eduvest - Journal of Universal Studies, 2024)
The government has initiated a lot of effort to control birthrate, and solve demographic issues as an endeavor to improve people’s quality of life. These program targets both women and men, but there is socially constructed idea that contraception is indeed a program made only for women. The imbalance participation between men and women inspires this research. Men has been less participating in family planning despite of the availability, more importantly in vasectomy. There are stigmas in the society about vasectomy and people who chose vasectomy. Therefore, the government establishes a community-based acceptor supporting group, that acts as an agent of change, to inspire, motivate, and educate people, under the name of Prio Utomo. This research uses case study as research method, and took place in Kecamatan Getasan, Kabupaten Semarang, Central Java, Indonesia, in which case the local Prio Utomo has been categorized as one of the most successful and achieved few rewards years priors.  Analysis result based on Persuasive Communication Theory shows that the motivator from Prio Utomo utilize two dominant appeal which are psychology appeal through achievement motives, and credibility appeal. More to that, Prio Utomo has been using both personal and interpersonal approach to promote and inspire people to choose or at least consider just the idea of vasectomy.  This research also found that the characteristic of people in some places might affect how well the idea and good message about vasectomy is being received.